Ochrona dziecka w sytuacji rozstania rodziców – konceptualizacja przedmiotu badań - Turczyk, Małgorzata (Rocznik Pedagogiczny, 2019)
The article is preconceptual in its nature, as it is an introduction to a planned research project in the area of pedagogy and law. The author describes the research in current trends in modern childhood studies, choosing the protection of children’s rights in the event of their parents’ separation as the basic research category. This category will be analyzed in ontological, epistemological and meth- odological dimensions. In view of the growing scale of family breakdowns, it becomes justified to ask a question about the way of experiencing, understanding and constructing knowledge about the subject of pedagogical and legal interactions – the child themself. Building knowledge about a child whose parents separate is not only intended to expand and build interdisciplinary theoretical knowl- edge, but also to provide a basis for designing adequate tools and activities to protect the rights of a child experiencing their parents’ separation. This article provides an outline of a research concept aimed at protecting children’s rights. The article contains extensive justifications for the research topic and the framework of the methodological concept.